A Survey on Analysis of Crime Detection Techniques Using Machine Learning - Kumar, Ashish; Singh, Kaptan; Saxena, Amit (International Journal of Computer Sciences and Engineering, 2022)
Finding the patterns from the huge collection of datasets is considered as one of the primary application of machine learning. Machine learning has already proved itself in transportation field and can be used in various other fields such as manufacturing, healthcare, investigation of crimes etc. Great advancement in technologies and societies has led to advancement in crimes and also the damage caused by them. It becomes even more difficult to prevent when the population in any area is concentrated and changes are rapid. That‘s why in many cities various crime prevention measures have been adopted as a part of smart city development. However, crimes can happen anywhere the need only is to determine the pattern of their occurrences which in turn can reduce the crime percentage. In order to provide society a better living crime investigation or analysis is considered as important application of machine learning. In this paper a survey has been done on analysis of crime and their prediction using machine learning techniques.